Fulfilling Ustaz Families’ Needs at the Al-Ashriyyah Nurul Imam Pesantren, Bogor, Indonesia: Between Hegemony and Independency - Aziz, Abdul; Hakim, Lukman; Nugraha, Iqbal Subhan (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2024)
Economic support from pesantren contributes to the ustaz families' stability, although it may create a dependency on their autonomy. This article discusses the financial support provided by pesantren and its dual impact on strength and independence within the ustaz families at the Al-Ashriyyah Nurul Iman Pesantren. Using empirical research with sociological methods, data are collected through in-depth interviews, observations, and documentation to gain insights into how this support affects their daily lives, economic stability, and sense of independence. Additionally, this article utilizes family resilience and hegemony theory. This article reveals that the facilities and allowance provided by the pesantren have a significant impact on the welfare of the ustaz families. Even though they appreciate what pesantren provided, some of them feel that there is a restriction on personal and family freedom, particularly in achieving economic self-sufficiency beyond the pesantren environment. This highlights a critical tension between financial security and autonomy that seems to be hegemonies.